Modeling the Dynamic Landscape Evolution of a Volcanic Coastal Environment Under Future Climate Trajectories - Manley, Kyle; Salles, T.; Müller, R. D. (Frontiers in Earth Science, 2020)
As anthropogenic forcing continues to rapidly modify worldwide climate, impacts on landscape changes will grow. Olivine weathering is a natural process that sequesters carbon out of the atmosphere, but is now being proposed as a strategy that can be artificially implemented to assist in the mitigation of anthropogenic carbon emissions. We use the landscape evolution model Badlands to identify a region (Tweed Caldera catchment in Eastern Australia) that has the potential for naturally enhanced supply of mafic sediments, known to be a carbon sink, into coastal environments. Although reality is more complex than what can be captured within a model, our models have the ability to unravel and estimate how erosion of volcanic edifices and landscape dynamics will react to future climate change projections. Local climate projections were taken from the Australian government and the IPCC in the form of four alternative pathways. Three additional scenarios were designed, with added contributions from the Antarctic Ice Sheet, to better understand how the landscape/dynamics might be impacted by an increase in sea level rise due to ice sheet tipping points being hit. Three scenarios were run with sea level held constant and precipitation rates increased in order to better understand the role that precipitation and sea level plays in the regional supply of sediment. Changes between scenarios are highly dependent upon the rate and magnitude of climatic change. We estimate the volume of mafic sediment supplied to the erosive environment within the floodplain (ranging from ∼27 to 30 million m3 by 2100 and ∼78–315 million m3 by 2500), the average amount of olivine within the supplied sediment under the most likely scenarios (∼7.6 million m3 by 2100 and ∼30 million m3 by 2500), and the amount of CO2 that is subsequently sequestered (∼53–73 million tons by 2100 and ∼206–284 million tons by 2500). Our approach not only identifies a region that can be further studied in order to evaluate the efficacy and impact of enhanced silicate weathering driven by climate change, but can also help identify other regions that have a natural ability to act as a carbon sink via mafic rock weathering.